Cognição distribuída e curso de ação - Jacques Theureau (Universidade do Porto, 2020)
The 'distributed cognition' research program, initiated by Edwin Hutchins, has contributed to the development of the 'course of action' research program from 1987 until now. Edwin Hutchins has recently recognized the proximity between his last researches, developed in terms of embodied and distributed cognition, and the enaction paradigm, followed by this 'course of action' research program. The question of the definition of an "augmented 'course of action' research program" is now raised. Such "program" should, in relation with this enaction paradigm, deepen and synthetize the past contributions of the 'distributed cognition' research program to the 'course of action' research program and add new contributions from it. Such deepening, synthesis, and renewal of the contributions to the 'course of action' research program are made easy by the mutual contribution and addition of different theoretical and methodological results obtained by the two research programs. We will present here our personal answer to this question.